Joy takes flight : a novel - Leon, Bonnie (Leon, Bonnie. Alaskan skies, 2012)
Newlyweds Kate and Paul are settling in their Alaska home in the bush country. They rejoice when Kate finds she is pregnant, but soon it is clear that there are hurdles ahead. Should she continue in her dangerous profession as an Alaskan bush pilot? Can she really fall into the traditional role of a wife? Then disaster strikes, life begins to unravel, and Kate fears she may have lost Paul for good.